Rubus laciniatus Willd. (Rosaceae), an introduced species new in the flora of the Republic of North Macedonia - Ćušterevska, Renata; Kostadinovski, Mitko; Matevski, Vlado (Macedonian Journal of Ecology and Environment, 2020)
Allochthonous species Rubus laciniatus Willd. is mentioned for the first time for the flora of the Republic of North Macedonia and represents its second finding in the Balkan Peninsula. The species was found during phytocenological research at the shores of the Prespa Lake. A brief description of the species with the more important morphological features, a description of the habitat where it was found, as well as a discussion of possible routes of introduction are given.